Musaical profiles and healthy ageing : mixed methods study towards developing a community music therapy intervention within care facilities for the elderly in Pretoria - Lotter, Carol Barbara (University of Pretoria, 2019)
Dissertation (MMus)--University of Pretoria, 2018.